The Trickster and the Engineer - Fredriksen, Lill Tove (Nordlit, 2018)
In the beginning of the 2000’s a meeting takes place at one of the major hospitals in Northern Norway, between a Sámi patient Juvvá, and his roommate, a retired Norwegian engineer. The engineer shows a negative attitude towards his Sámi roommate. Based on a symptomatic reading of three stories, this article presents a character analysis of Juvvá’s birgengoansttat, coping skills, in his encounter with the engineer. The analysis focuses on Juvvá as a trickster figure representing the Sámi people, and the engineer as stállu, a set of structures that represent the majority’s values system. The engineer’s negative mindset towards his Sámi roommate represents the shadow of centuries of repression and lack of knowledge about Sámi language, culture and history. The Norwegian government’s assimilation politics, the Norwegianization policies, function as the contextual backdrop for the investigation and of the reactions of the engineer. In my role as a scholar and mediator of the stories, I also function as a character in this investigation, at a meta level. This requires some focus on the context that frames my reading. The analysis of the stories reveals how non-verbal communication and humor are used to show resistance towards derogatory attitudes in the majority system. Juvvá’s agency is to cope, and take control of his own situation in the narrative of the hospital’s white world. In his role as a trickster, Juvvá represents a boundary-crossing figure and demonstrates a flexibility in finding a creative space to exercise his abilities to coping in the meeting with his hostile roommate.